Duma i uprzedzenie jak historia romantyczna. O adaptacji powieści Jane Austen w reżyserii Joe Wrighta - Pilawska, Roksana (Przestrzenie Teorii, 2019)
Pilawska Roksana, Duma i uprzedzenie jak historia romantyczna. O adaptacji powieści Jane Austen w reżyserii Joe Wrighta [Dirty (un)Romantic story. An Analysis of Aesthetic Aspects in the Film Adaptation of Pride and Prejudice Directed by Joe Wright]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 417–431. ISSN 1644-6763. DOI 10.14746/pt.2019.32.23. The aim of my study is to attempt a comparative analysis of the two most famous film adaptations of the bestselling novel by Jane Austen, Pride and Prejudice. As research material, I chose the mini-series produced by the BBC in 1995, which was part of the then popular trend of heritage films (heritage cinema) and the feature film from 2005, directed by Joe Wright, which, in the opinion of film experts, was a completely new form of audiovisual presentation of Austen’s work. In the article, I focus only on interpreting the aesthetic aspects of both productions, which would indicate similarities and differences, thus showing numerous shifts of emphasis in the aesthetic layer of the newer version.